U.S. policies toward Iran and implications for regional security in the Persian Gulf 1979-2008 - Mirhosseini, Seyed Mohsen (2012)
This research examined the US policies toward Iran and its implications on regional security in the Persian Gulf during the period from 1979 – 2008. In addition, the study also evaluated the U.S. policies toward Iran in relations to the Persian Gulf during the presidencies of Carter, Reagan, George HW Bush, Clinton, and George Bush during this period of time. The objectives of the research were achieved by seeking answers to the two research questions: 1) What were the evolutions of the U.S. regional security policies regarding Iran in the Persian Gulf from 1979 to 2008?; 2) What were the influences of the U.S. regional security policies on the regional peace and stability regarding Iran in the Persian Gulf? Based on the research questions, the goals of this study were to examine and analyze the security policies of different US administrations from the time of the Islamic revolution in 1979 until the end of the George W. Bush presidency in 2008. In other words, the main focus of the study was to understand the security policies of the US administrations during the period from 1979 to 2008 toward Iran in the Persian Gulf region. Therefore, the study attempted to evaluate these security policies to identify and explain the factors of success or failure of these policies in the Persian Gulf region and to finally determine the security status of the Persian Gulf. As such, evaluating the thrust of various US policies toward Iran in the Persian Gulf region will show the success or failure of the US to create peace and security in the region. For this purpose, the qualitative approach was selected and applied to the study and the data were collected from official websites available on the internet. Such data comprised the speeches of the Iranian and American administrations, official records and documents on security policies of the US toward Iran in the Persian Gulf region including the Arms Export Control Act, U.S. Congress negotiations, US Department of State annual reports, Country Reports on Terrorism, Peterson Institute Documents, and Middle East policy council documents. Thus, the goal of using the qualitative approach was to obtain an in-depth understanding of the security policies of the US toward Iran in the Persian Gulf region during the specified period. The analysis of the data revealed that the unilateral security policies of different US administrations toward Iran in the Persian Gulf did not succeed in establishing stability and peace for the region. Based on the conclusions of the research, the three main findings are outlined as follows: Firstly, the findings of the current study about the U.S. policies toward Iran in relation to the Persian Gulf region since the Islamic Revolution of Iran in 1979 show that these policies were always confronted by challenges from local states such as Iran and Iraq and in some cases, a few regional conservative Arab states such as Saudi Arabia. This implies the failure of the unilateral U.S. security policies in the Persian Gulf region. Secondly, the analysis of the ―Regional Security Complex Theory‖ proves that according to the ―Regional Security Complex Theory‖, there were significant relationships between the rivalries of the regional states in the Persian Gulf and external interventions. The results revealed that local rivalries led to the interference by external powers in the region. In the case of Iran, the rivalries inside the Gulf Cooperation Council states and between them and Iran and Iraq led to U.S. intervention in the region. Moreover, the results obtained from application of the theory to the realities of the region revealed that the only reasonable solution for the security problems of the Persian gulf region is a collective security forum that involves all the states of this important area including the GCC states, Iran and Iraq (6+2 arrangement). Finally, the findings of this study have important implications for the promotion of peace and security in the Persian Gulf region. As the results showed, the various direct and indirect U.S policies toward Iran related to the Persian Gulf were unable to enhance American demands for a stable condition to maintain their interest in the region. Furthermore, the U.S. policies could not stop Iran‘s ambitions to have a collective security policy that involved all the Persian Gulf states in a forum. So the findings of this study suggest that to stabilize the region, there should be multilateral relations between Iran, Iraq, the GCC and U.S. that consider the concerns of all parties and the participation of all local states for peace and security to be achievable in the region.